Analyzing students’ errors on the topic of statistics using Watson’s criteria - Rachmawati Khaerun Nisa; Dahlan, Jarnawi Afgani (CV. Pustaka Literasi Ilmiah, 2025)
This research is titled “Analyzing students’ errors on the topic of statistics using Watson’s criteria” which aims to identify in depth the mistakes made by students in solving statistics problems. This study uses a qualitative approach with a descriptive method, so the results obtained emphasize more on descriptive explanations regarding the forms and types of errors that occur. The research subjects were 12th-grade students at Madrasah Aliyah AL AMIN, Kuningan Regency, who were chosen because they were considered to have received statistical material but still encountered various obstacles in the learning process. Research data were obtained through written tests and interviews designed to further explore the reasons why students made errors. Based on the analysis, it was found that student errors can be categorized into eight Watson criteria, including incorrect procedures, missing data, manipulation errors, and errors in interpreting problems. Although some students are able to arrive at the correct answers, the process of solving problems is often not systematic and skips important steps, indicating weaknesses in understanding basic statistics concepts. These findings suggest that improvements are still needed in teaching approaches so that students not only focus on the final results but also understand the problem-solving process thoroughly. By understanding the dominant types of errors, educators can develop more targeted learning strategies, provide constructive feedback, and create more comprehensive evaluation methods. This research is expected to contribute to curriculum development and enhance the quality of statistics education, enabling students to achieve better learning outcomes.